2005
DOI: 10.1902/jop.2005.76.11.1871
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Miller Class I and II Recession Defects Using Enamel Matrix Proteins Versus Coronally Advanced Flap Technique: A 2‐Year Report

Abstract: Enamel matrix derivative seems to provide better long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(139 citation statements)
references
References 49 publications
5
118
0
12
Order By: Relevance
“…They obtained slightly better outcomes with CPF‫ם‬EMD in terms of root coverage and clinical attachment level than with CPF, but the differences were not statistically significant. Other studies 6,7,20) involving more cases and longer follow-up periods also found no significant differences between CPF and CPF‫ם‬EMD. Meanwhile, several studies 3,5,18) have shown significantly better outcomes with CPF‫ם‬EMD than with CPF in terms of percentage of root coverage, keratinized gingival gain, and attachment gain, revealing substantial variability in the outcomes of long-term studies of CPF‫ם‬EMD.…”
Section: Discussionmentioning
confidence: 82%
“…They obtained slightly better outcomes with CPF‫ם‬EMD in terms of root coverage and clinical attachment level than with CPF, but the differences were not statistically significant. Other studies 6,7,20) involving more cases and longer follow-up periods also found no significant differences between CPF and CPF‫ם‬EMD. Meanwhile, several studies 3,5,18) have shown significantly better outcomes with CPF‫ם‬EMD than with CPF in terms of percentage of root coverage, keratinized gingival gain, and attachment gain, revealing substantial variability in the outcomes of long-term studies of CPF‫ם‬EMD.…”
Section: Discussionmentioning
confidence: 82%
“…This regenerative concept has also been demonstrated in root coverage procedures (24). EMD associated with CAF was shown to increase the percentage of root coverage (25).…”
Section: Introductionmentioning
confidence: 86%
“…Additional application of EMD, however, induced a statistically significantly greater formation of keratinized tissue, compared to that with coronally positioned flap alone [130] . A follow-up evaluation of this study showed that over 2 years, complete root coverage could be maintained in 53% of the EMD group compared to the control (23%) [131] . However, in the second year after therapy as many as 47% of the control group had deteriorated compared to only 22% in the treatment group.…”
Section: Controlled Clinical Studies In Recession Defectsmentioning
confidence: 66%
“…The available data suggest that the use of EMD may enhance the outcome of root coverage procedures, but the additional application of a connective tissue graft seems to further enhance the formation of keratinized tissue [134][135][136] . It is interesting to note that most controlled clinical studies evaluating the treatment of gingival recessions with coronally repositioned flaps and EMD therapy reported stable clinical results after a longer time period, up to 2 years, and an increase in the width of keratinized tissue, thus indicating that EMD may have an effect upon the proliferation and keratinization of gingival fibroblasts [131,137,138] .…”
Section: Controlled Clinical Studies In Recession Defectsmentioning
confidence: 99%